Macrophages as an Emerging Source of Wnt Ligands: Relevance in Mucosal Integrity - Cosin-Roger, Jesús; Ortiz-Masià, Mª Dolores; Barrachina, Mª Dolores (Frontiers in Immunology, 2019)
The Wnt signalling pathway is a conserved pathway involved in important cellular processes such as the control of embryonic development, cellular polarity, cellular migration and cell proliferation. In addition to playing a central role during embryogenesis, this pathway is also an essential part of adult homeostasis. Indeed, it controls the proliferation of epithelial cells in different organs such as intestine, lung, and kidney, and guarantees the maintenance of the mucosa in physiological conditions. The origin of this molecular pathway is the binding between Wnt ligands (belonging to a family of 19 different homologous secreted glycoproteins) and their specific membrane receptors, from the Frizzled receptor family. This specific interaction triggers the activation of the signalling cascade, which in turn activates or suppresses the expression of different genes in order to change the behaviour of the cell. On the other hand, alterations of this pathway have been described in pathological conditions such as inflammation, fibrosis and cancer. In recent years, macrophages - among other cell types - have emerged as a potential source of Wnt ligands. Due to their high plasticity, macrophages, which are central to the innate immune response, are capable of adopting different phenotypes depending on their microenvironment. In the past, two different phenotypes were described: a proinflammatory phenotype - M1 macrophages - and an anti-inflammatory phenotype - M2 macrophages - and a selective expression of Wnt ligands has been associated with said phenotypes. However, nowadays it is assumed that macrophages in vivo move through a continual spectrum of functional phenotypes. In both physiological and pathological (inflammation, fibrosis and cancer) conditions, the accumulation and polarization of macrophages conditions the future of the tissue, facilitating various scenarios, such as resolution of inflammation, activation of fibrosis, and cancer development due to the modulation of the Wnt signalling pathway, in autocrine and paracrine manner. In this work, we provide an overview of studies that have explored the role of macrophages and how they act as a source of Wnt ligands and as mediators of mucosal integrity.